Regional and temporal climatic classification for Borneo - Ramzah Dambul,; Phil Jones, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
This paper describes a regional and temporal climate classification which is an attempt to divide the Borneo region into several homogenous groups based on long-term average climatic behaviour. One the one hand, the method of the regional classification used is one where the result of the regional classification should not be affected by the changes in climate. On the other, the method of temporal classification adopted is to group each individual day into one of several identified modes. These modes, which will be changing on daily basis are described by specific spatial patterns of climatic variables (precipitation and temperature). Although these two regional and temporal classifications are created from different variables and different methods, they are mutually complementary and describe the local climate in Borneo. It was found that certain types of weather might be more associated with certain groups of climatic divisions. Thus while spatial climatic variations in Samarahan Climatic Group (B1)describe the unique pattern of weather Type 3 (Western Wet), those of Type 4 (Central Wet) and Type 5(Eastern Wet) are more closely associated with the climate variability for Sepanggar (A1) and Sepilok (A2) groups